Review article: The role of Tonsils in promoting infection - Imad Ibrahim Ali Al-Sultan; Kulthom H; Tarik Ibrahem Ali; Ahmed G.Alattraqch (Design for Scientific Renaissance, 2013)
Tonsil microbial flora plays a distinct role in the process of infection. The relationship between the commensalism germs that live inside the living creature and the mechanism of development that causes illness is unknown. Most studies on the comparison of infected and non-infected tonsils based on certain polymicrobial and host factors. The germs share our biological systems from birth to death with the specificity of commensalism phenomena. Difference in flora retrieved from tonsil surface and core samples in diagnostic investigation promote to new understanding of infection mechanisms and causes of illness. This review article discusses the possibilities of infection existence by normal inhabitant biological agents.